Squamous Cell Carcinoma of the Lacrimal Sac: A Case Report - Siriwanasan R. (2014)
Lacrimal sac tumors are rare tumors of the periorbital region. The authors report a case of squamous cell carcinoma of the lacrimal sac in a 47-year-old Thai man. The patient presented with epiphora and a palpable mass in the medial canthal area. The diagnosis was confirmed by the pathological studies. Radical surgery and radiation therapy were given. Early detection and long-term follow-up are necessary.